A hydrophobic aramid coating solution for lithium-ion batteries, a coated separator, and a preparation method thereof.

By applying hydrophobic aramid coating liquid on the lithium-ion battery separator, the problem of easily piercing the battery separator during circulation is solved, and the effect of reducing the battery weight, improving cycle stability and low-temperature discharge performance is achieved.

CN119307175BActive Publication Date: 2025-04-22TAYHO BATTERY MATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411832611.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-22
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

During the circulation of lithium-ion batteries, the growth of the negative electrode lithium dendrites is prone to pierce the diaphragm, resulting in short circuits, ultra-high temperatures and even fire, posing serious safety hazards. The prior art reduces the energy density by coating the separator with inorganic alumina or silica, but increases the battery weight.

Method used

A hydrophobic aramid coating liquid of lithium-ion battery is used to prepare an aramid-coated membrane with hydrophobic function by uniformly coating on the base film and molding, washing, drying and shaping through a solidification bath. The coating liquid is mixed with DPMIA and PMIA polymerization liquid, diluted with organic solvent, and the solid content is 3 wt%-15 wt%, to reduce the moisture of the separator, improve the coating speed and drying efficiency.

Benefits of technology

It realizes the reduction of the moisture of the coated diaphragm, accelerates the coating speed, reduces drying temperature and energy consumption, and improves the cycle stability and low-temperature discharge performance of the battery, and obtains a coated diaphragm with excellent comprehensive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307175B_ABST
    Figure CN119307175B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of battery materials, and specifically to a hydrophobic aramid coating liquid, a coating diaphragm and a preparation method for a lithium ion battery. The preparation method is as follows: a diphenyl aromatic diamine monomer and isophthaloyl chloride are subjected to a polycondensation reaction in an organic solvent, and a DPMIA polymer solution is obtained by neutralization and degassing; a metaphenylenediamine monomer and isophthaloyl chloride are subjected to a polycondensation reaction in an organic solvent, and a PMIA polymer solution is obtained by neutralization and degassing; the DPMIA polymer solution and the PMIA polymer solution are mixed and diluted with an organic solvent to obtain the coating liquid. The coating liquid is uniformly coated on a base film, formed by a coagulation bath, and then washed, dried, shaped and rolled to prepare a hydrophobic aramid coating diaphragm. The coating liquid can greatly reduce the water content of the coating diaphragm off the machine, speed up the coating speed of aramid on the machine, reduce the drying temperature of the drying section, shorten the drying time, reduce energy consumption, and at the same time show the advantages of low-temperature discharge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hydrophobic aramid coating liquid, a coating diaphragm and a preparation method for a lithium ion battery, belonging to the technical field of battery materials. Background Art

[0002] Lithium-ion batteries have the advantages of high voltage, high specific energy, long cycle life, and long storage time. They are widely used in energy storage power systems (such as thermal, hydropower, wind and solar power stations), power tools, electric bicycles, electric motorcycles, electric vehicles, etc. During the cycle of lithium-ion batteries, the growth of negative lithium dendrites can easily pierce the diaphragm, causing a short circuit, instantaneously generating a large amount of heat, igniting the electrolyte, causing the battery to overheat or even catch fire, posing a huge safety hazard.

[0003] At present, a layer of inorganic aluminum oxide (Al2O3) is often coated on a polyethylene (PE) base film or a polypropylene (PP) base film. 2 O 3 ) powder or silicon dioxide (SiO 2 ) to improve the puncture resistance and heat resistance of lithium-ion battery separators, but it will increase the weight of the battery, thereby reducing the battery energy density. Many teams have further developed polymer (such as polymethyl methacrylate (PMMA), meta-aramid (PMIA), para-aramid (PPTA), polyvinylidene fluoride (PVDF), polyimide (PI), etc.) coating separator methods, such as Chinese patent applications CN117060007A, CN118431664A, etc.

[0004] The full name of meta-aramid (PMIA) is poly(m-phenylene isophthalamide), also known as aramid 1313, density: 1.33~1.36g / cm 3 . Meta-aramid is prepared by polycondensation reaction, and the reaction monomers are isophthaloyl chloride (IPC) and meta-phenylenediamine (MPD). The amide group in meta-aramid is interconnected with the meta-phenyl group, and the hydrogen bonds are arranged in a lattice on the two planes of the crystal, with strong interaction forces, which makes the molecular structure of PMIA very stable and has excellent flame retardancy, heat resistance and chemical stability. Precisely because PMIA has such obvious advantages, it has a very broad application prospect as a new generation of battery separators, but because the material itself has a certain water absorption, the moisture content of the coated separator is higher than that of conventional ceramic membranes, which has an adverse effect on the subsequent battery cell process and overall performance. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a hydrophobic aramid coating liquid for a lithium ion battery, a coating diaphragm and a preparation method thereof. The coating liquid can greatly reduce the moisture of the coating diaphragm when it leaves the machine, speed up the coating speed of the aramid on the machine, reduce the drying temperature of the drying section, shorten the drying time, reduce energy consumption, and at the same time demonstrate the advantage of low-temperature discharge.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a hydrophobic aramid coating liquid for a lithium ion battery, the preparation method comprising:

[0007] S1. Preparation of DPMIA polymerization solution and PMIA polymerization solution:

[0008] Preparation of DPMIA polymer solution: biphenyl aromatic diamine monomer and isophthaloyl chloride are subjected to polycondensation reaction in an organic solvent, and DPMIA polymer solution is obtained after neutralization and degassing;

[0009] Preparation of PMIA polymer solution: m-phenylenediamine monomer and isophthaloyl chloride are subjected to polycondensation reaction in an organic solvent, and then neutralized and degassed to obtain PMIA polymer solution;

[0010] S2. Preparation of coating liquid: DPMIA polymerization liquid and PMIA polymerization liquid are mixed and diluted with an organic solvent to obtain the coating liquid.

[0011] Further, the biphenyl aromatic diamine monomer is 2,2'-bis-[4-(4-aminophenoxy)phenyl]propane, 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2-bis[4-(4-aminophenoxy)-phenyl]-hexafluoropropane, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,4-bis(2,4-diaminophenoxy)benzene, 2,2-bis(4-aminophenoxy)biphenyl, 4,4'-bis (4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)diphenyl sulfone, 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl, 2,2'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl, 4,4'-bis(4-amino-2-trifluoromethylphenoxy)diphenyl sulfone, 1,3-bis(2-trifluoromethyl-4-aminophenoxy)benzene, 2-(3-aminophenyl)-1,3-benzoxazol-5-amine, N,N'-[2,2'-bis(trifluoromethyl)]-[1,1'-biphenyl]- 4,4'-diacyl]bis[4-aminobenzene], 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, 2,2'-bis[4-(5-amino-2-pyridylphenoxy)phenyl]propane, 4,4'-bis(4-aminophenoxy)diphenyl sulfone, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-nitrophenoxy)biphenyl, 2,2'-bis[4-( any one of: 1,4'-bis(4-amino-2-trifluoromethylphenyl)piperazine, 2,2-bis(4-nitrophenoxy)]propane, 2,2-bis(4-aminophenyl)hexafluoropropane, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,5-diaminobenzoic acid, 1,3,5-tris(4-aminophenoxy)benzene, 1,3,5-tris(2-trifluoromethyl-4-aminophenoxy)benzene, 3-aminobenzohydrazide, and 1,4'-bis(4-amino-2-trifluoromethylphenyl)piperazine.

[0012] Further, in the coating solution, the mass ratio of DPMIA to PMIA is (5-10): (90-95);

[0013] The solid content of the coating liquid is 3wt%-15wt%.

[0014] Furthermore, the organic solvent is at least one of DMAc, DMF, NMP and DMSO.

[0015] Furthermore, when preparing the DPMIA polymerization solution, the molar ratio of the biphenyl aromatic diamine monomer to isophthaloyl chloride is 1:(1-1.05), and isophthaloyl chloride is added to the reaction system in batches for polycondensation reaction, and the polycondensation reaction temperature is 45-55°C;

[0016] When preparing PMIA polymerization liquid, the molar ratio of m-phenylenediamine monomer to isophthaloyl chloride is 1:(1-1.05), and isophthaloyl chloride is added to the reaction system in batches for polycondensation reaction, and the polycondensation reaction temperature is 45-55°C.

[0017] The invention also discloses a hydrophobic aramid coating liquid for a lithium ion battery. The coating liquid is prepared according to the preparation method of the invention.

[0018] The present invention also discloses a method for preparing a hydrophobic aramid coated diaphragm for a lithium ion battery, the preparation method comprising: uniformly coating a coating liquid on a base film, forming the base film through a coagulation bath, and then washing, drying, shaping, and rolling the base film to prepare the hydrophobic aramid coated diaphragm;

[0019] The coating liquid is prepared according to the preparation method of the present invention.

[0020] Furthermore, the coagulation bath is an aqueous solution of an organic solvent, the mass concentration of the organic solvent in the coagulation bath is 60%-80%, and the temperature of the coagulation bath is 10-20°C.

[0021] Furthermore, the water washing temperature is 20-40°C; the drying temperature is 55-85°C, the drying speed is 50-120m / min; and the setting temperature is 55-85°C.

[0022] The invention also discloses a hydrophobic aramid coated diaphragm for a lithium ion battery. The coated diaphragm is prepared according to the preparation method of the invention.

[0023] The beneficial effects of the present invention are:

[0024] (1) The method for preparing the coating liquid of the present invention is to modify the polymerization solution by introducing a diphenyl aromatic diamine monomer to obtain an aramid polymerization liquid with a hydrophobic function. The coating liquid prepared by this method increases the intermolecular polarity by extending the distance between the amide bonds, and on the other hand, it weakens the hydrogen bonding effect while retaining a certain degree of wettability to reduce the hydrophilicity of the aramid coating. The aramid with a hydrophobic function is mixed with conventional aramid in a certain proportion and then coated on both sides of the base film by roller coating. After non-solvent phase conversion, water washing, drying and shaping, an aramid coated diaphragm with a hydrophobic function is obtained. The advantage of this functional diaphragm is that it greatly reduces the water content of the coated diaphragm, which can speed up the coating speed of the aramid on the machine, reduce the drying temperature of the drying section, shorten the drying time, reduce energy consumption, and show the advantage of low-temperature discharge. At the same time, the hydrophobic aramid coated diaphragm prepared by this technology has a low water content, which can reduce the side reactions at the interface of the electrode material and is beneficial to improve the cycle stability of the battery.

[0025] (2) In the method for preparing the coating liquid and the coated membrane of the present invention, by controlling the addition ratio of the DPMIA polymer solution and matching the appropriate coagulation bath conditions of the coated membrane, the coated membrane has good tensile strength, peel strength, thermal stability and air permeability while having good hydrophobic properties. Thus, a coated membrane with excellent comprehensive performance is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a process flow chart for preparing the coated diaphragm;

[0027] Figure 2 This is the SEM image of the coated diaphragm prepared in Example 1. DETAILED DESCRIPTION

[0028] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0030] A method for preparing a hydrophobic aramid coating liquid for a lithium ion battery, the preparation method comprising:

[0031] S1. Preparation of DPMIA polymerization solution and PMIA polymerization solution:

[0032] Preparation of DPMIA polymer solution: biphenyl aromatic diamine monomer and isophthaloyl chloride are subjected to polycondensation reaction in an organic solvent, and DPMIA polymer solution is obtained after neutralization and degassing;

[0033] Preparation of PMIA polymer solution: m-phenylenediamine monomer and isophthaloyl chloride undergo polycondensation reaction in an organic solvent, and then undergo neutralization and degassing to obtain PMIA (polymethylene isophthalamide) polymer solution;

[0034] S2. Preparation of coating liquid: DPMIA polymerization liquid and PMIA polymerization liquid are mixed and diluted with an organic solvent to obtain the coating liquid.

[0035] Specifically, the biphenyl aromatic diamine monomer is 2,2'-bis-[4-(4-aminophenoxy)phenyl]propane, 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2-bis[4-(4-aminophenoxy)-phenyl]-hexafluoropropane, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,4-bis(2,4-diaminophenoxy)benzene, 2,2-bis(4-aminophenoxy)biphenyl, 4,4'-bis( 4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)diphenyl sulfone, 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl, 2,2'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl, 4,4'-bis(4-amino-2-trifluoromethylphenoxy)diphenyl sulfone, 1,3-bis(2-trifluoromethyl-4-aminophenoxy)benzene, 2-(3-aminophenyl)-1,3-benzoxazol-5-amine, N,N'-[2,2'-bis(trifluoromethyl)]-[1,1'-biphenyl]- 4,4'-diacyl]bis[4-aminobenzene], 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, 2,2'-bis[4-(5-amino-2-pyridylphenoxy)phenyl]propane, 4,4'-bis(4-aminophenoxy)diphenyl sulfone, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-nitrophenoxy)biphenyl, 2,2'-bis[4-( any one of: 1,4'-bis(4-amino-2-trifluoromethylphenyl)piperazine, 2,2-bis(4-nitrophenoxy)]propane, 2,2-bis(4-aminophenyl)hexafluoropropane, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,5-diaminobenzoic acid, 1,3,5-tris(4-aminophenoxy)benzene, 1,3,5-tris(2-trifluoromethyl-4-aminophenoxy)benzene, 3-aminobenzohydrazide, and 1,4'-bis(4-amino-2-trifluoromethylphenyl)piperazine.

[0036] Specifically, in the coating solution, the mass ratio of DPMIA to PMIA is (5-10): (90-95);

[0037] The solid content of the coating liquid is 3wt%-15wt%.

[0038] Specifically, the organic solvent is at least one of DMAc, DMF, NMP and DMSO.

[0039] Specifically, when preparing the DPMIA polymerization solution, the molar ratio of the biphenyl aromatic diamine monomer to isophthaloyl chloride is 1: (1-1.05), and isophthaloyl chloride is added to the reaction system in batches for polycondensation reaction, and the polycondensation reaction temperature is 45-55°C;

[0040] When preparing PMIA polymerization liquid, the molar ratio of m-phenylenediamine monomer to isophthaloyl chloride is 1:(1-1.05), and isophthaloyl chloride is added to the reaction system in batches for polycondensation reaction, and the polycondensation reaction temperature is 45-55°C.

[0041] More specifically, when preparing the DPMIA polymerization solution and the PMIA polymerization solution, the isophthaloyl chloride is added in 2-3 times, and the time interval between two adjacent additions of isophthaloyl chloride is 1-2 hours.

[0042] More specifically, after the polycondensation reaction is completed, a neutralizing agent is added to adjust the pH of the system to 7-8. The neutralizing agent used in the embodiment of the present invention is sodium carbonate, but is not limited to this one.

[0043] A hydrophobic aramid coating liquid for a lithium ion battery, wherein the coating liquid is prepared according to the preparation method of the present invention.

[0044] A method for preparing a hydrophobic aramid coated diaphragm for a lithium ion battery, the preparation method comprising: uniformly coating a coating liquid on a base film, forming the film through a coagulation bath, and obtaining a coated diaphragm having an aramid coating structure through a non-solvent induced phase separation method, that is, forming a film on the surface of the base material, and then washing, drying, shaping, and winding to prepare a hydrophobic aramid coated diaphragm; the coating liquid is prepared according to the preparation method of the present invention. The preparation process of the coated diaphragm is as follows Figure 1 shown.

[0045] Specifically, the coagulation bath is an aqueous solution of an organic solvent, the mass concentration of the organic solvent in the coagulation bath is 60%-80%, and the temperature of the coagulation bath is 10-20°C.

[0046] Specifically, the water washing temperature is 20-40°C; the drying temperature is 55-85°C, the drying speed is 50-120 m / min; and the setting temperature is 55-85°C.

[0047] More specifically, the base film is a base film commonly used in lithium-ion battery separators. The base film used in the embodiment of the present invention is a 7 μm polyethylene base film, but it is not limited to use only this kind of base film.

[0048] A hydrophobic aramid coated diaphragm for a lithium ion battery, wherein the coated diaphragm is prepared according to the preparation method of the present invention.

[0049] Example 1

[0050] (1) In a nitrogen-dried environment, add biphenyl aromatic diamine (2,2'-bis-[4-(4-aminophenoxy)phenyl]propane) and DMAc to a 500ml glass reactor at room temperature. After the biphenyl aromatic diamine is dissolved, the temperature in the system is maintained at 15°C. Then add isophthaloyl chloride to the system for polycondensation reaction I. During the reaction, the stirrer is kept at a speed of 500r / min. The isophthaloyl chloride added in the polycondensation reaction I is 90% by weight of the total amount of isophthaloyl chloride added. During the reaction, the system temperature is 45°C and the reaction time is 30min. Then, add the remaining 10% by weight of isophthaloyl chloride to the system for polycondensation reaction II. During this process, the system temperature is controlled at 55°C and the reaction time is 15min. After the polycondensation reaction is completed, add a neutralizer to the system and adjust the pH value of the system to 7.0. After neutralization reaction, DPMIA polymer solution was obtained with a viscosity of 2100 Pa•s and a molecular weight distribution of Mw / Mn=1.35. The solid content of DPMIA polymer solution was 22%, and the molar ratio of diphenyl aromatic diamine to isophthaloyl chloride during the preparation of DPMIA polymer solution was 1:1.

[0051] (2) Under nitrogen dry environment, m-phenylenediamine and DMAc were added to a 500ml glass reactor at room temperature. After m-phenylenediamine was dissolved, the temperature in the system was maintained at 15°C. Then, isophthaloyl chloride was added to the system for polycondensation reaction I. During the reaction, the stirrer maintained a speed of 500r / min. The isophthaloyl chloride added in polycondensation reaction I was 90% by weight of the amount of acyl chloride added. During the reaction, the system temperature was controlled at 45°C and the reaction time was 30min. Then, the remaining 10% by weight of isophthaloyl chloride was added to the system for polycondensation reaction II. During this process, the system temperature was controlled at 55°C and the reaction time was 15min. After the polycondensation reaction was completed, a neutralizer was added to the system to adjust the pH value of the system to 8.0. After the neutralization reaction, PMIA polymer solution was obtained with a viscosity of 800 Pa•s and a molecular weight distribution of Mw / Mn=1.43. The solid content of the PMIA polymerization solution is 20%, and the molar ratio of m-phenylenediamine to m-phthaloyl chloride during the preparation of the PMIA polymerization solution is 1:1.05.

[0052] (3) The DPMIA polymer solution and the PMIA polymer solution were mixed, wherein the solid weight ratio of DPMIA to PMIA was 5:95; DMAc was then added for dilution to obtain a coating solution with a solid content of 9 wt %.

[0053] (4) The coating liquid was coated on a coating machine at a coating speed of 60 m / min, and then formed in a coagulation bath, wherein the DMAc content in the coagulation bath was 70% and the temperature was 15°C. A coated diaphragm with an aramid coating structure was obtained by a non-solvent induced phase separation method. After washing with water at 30°C, drying at 65°C, shaping at 80°C, and winding, an aramid coated diaphragm with hydrophobic functional properties was prepared, and the moisture content off the machine was 1711.3 ppm.

[0054] Example 2

[0055] (1) In a nitrogen-dried environment, add biphenyl aromatic diamine (2,2'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl) and DMAc to a 500ml glass reactor at room temperature. After the biphenyl aromatic diamine is dissolved, the temperature in the system is maintained at 15°C. Then add isophthaloyl chloride to the system for polycondensation reaction I. During the reaction, the stirrer is kept at a speed of 500r / min. The isophthaloyl chloride added in the polycondensation reaction I is 90% by weight of the total amount of isophthaloyl chloride added. During the reaction, the system temperature is 45°C and the reaction time is 30min. Then, add the remaining 10% by weight of isophthaloyl chloride to the system for polycondensation reaction II. During this process, the system temperature is controlled at 55°C and the reaction time is 15min. After the polycondensation reaction is completed, add a neutralizer to the system and adjust the pH value of the system to 7.0. After neutralization reaction, DPMIA polymer solution was obtained with a viscosity of 1800 Pa•s and a molecular weight distribution of Mw / Mn=1.37. The solid content of DPMIA polymer solution was 11%, and the molar ratio of diphenyl aromatic diamine to isophthaloyl chloride in the preparation process of DPMIA polymer solution was 1:1.02.

[0056] (2) Same as step (2) in Example 1.

[0057] (3) The DPMIA polymer solution and the PMIA polymer solution were mixed, wherein the solid weight ratio of DPMIA to PMIA was 10:90, and then DMAc was added for dilution to obtain a coating solution with a solid content of 9 wt %.

[0058] (4) The coating liquid is coated on a coating machine at a coating speed of 60 m / min, and is formed through a coagulation bath, wherein the DMAc content in the coagulation bath is 60% and the temperature is 10°C. A coated diaphragm with an aramid coating structure is obtained through a non-solvent induced phase separation method. The aramid coated diaphragm is washed with water at 20°C, dried at 70°C, shaped at 85°C, and rolled up to prepare an aramid coated diaphragm with hydrophobic functional properties. The moisture content off the machine is 1536.6 ppm.

[0059] Example 3

[0060] (1) Under nitrogen dry environment, add biphenyl aromatic diamine (1,4-bis(4-aminophenoxy)benzene) and NMP into a 500ml glass reactor at room temperature. After the biphenyl aromatic diamine is dissolved, the temperature in the system is maintained at 15°C. Then add isophthaloyl chloride to the system for polycondensation reaction. During the reaction, the stirrer maintains a speed of 500r / min. The isophthaloyl chloride added in the polycondensation reaction is 90% by weight of the total amount of isophthaloyl chloride added. During the reaction, the system temperature is 45°C and the reaction time is 30min. Then add the remaining 10% by weight of isophthaloyl chloride to the system for polycondensation reaction. During this process, the system temperature is controlled at 55°C and the reaction time is 15min. After the polycondensation reaction, add a neutralizer to the system and adjust the pH value of the system to 7.5. After the neutralization reaction, a DPMIA polymer solution is obtained with a viscosity of 1400 Pa•s and a molecular weight distribution of Mw / Mn=1.36. The solid content of the DPMIA polymerization solution is 18%, and the molar ratio of diphenyl aromatic diamine and isophthaloyl chloride in the preparation process of the DPMIA polymerization solution is 1:1.05.

[0061] (2) Under nitrogen dry environment, m-phenylenediamine and NMP were added to a 500ml glass reactor at room temperature. After m-phenylenediamine was dissolved, the temperature in the system was maintained at 15°C. Then, isophthaloyl chloride was added to the system for polycondensation reaction I. During the reaction, the stirrer maintained a rotation speed of 500r / min. The isophthaloyl chloride added in polycondensation reaction I was 90% by weight of the amount of acyl chloride added. During the reaction, the system temperature was controlled at 45°C and the reaction time was 30min. Then, the remaining 10% by weight of isophthaloyl chloride was added to the system for polycondensation reaction II. During this process, the system temperature was controlled at 55°C and the reaction time was 15min. After the polycondensation reaction was completed, a neutralizer was added to the system to adjust the pH value of the system to 8.0. After the neutralization reaction, PMIA polymer solution was obtained with a viscosity of 820 Pa•s and a molecular weight distribution of Mw / Mn=1.44. The solid content of the PMIA polymerization solution is 19%, and the molar ratio of isophthaloyl chloride to metaphenylenediamine during the preparation of the PMIA polymerization solution is 1:1.

[0062] (3) Mixing the DPMIA polymer solution and the PMIA polymer solution, wherein the solid weight ratio of DPMIA to PMIA is 5:95; then adding NMP for dilution to obtain a coating solution with a solid content of 15 wt %.

[0063] (4) The coating liquid is coated on a coating machine at a coating speed of 120 m / min, and is formed through a coagulation bath, wherein the NMP content in the coagulation bath is 80% and the temperature is 20°C. A coated diaphragm with an aramid coating structure is obtained through a non-solvent induced phase separation method. The aramid coated diaphragm is washed with water at 40°C, dried at 85°C, shaped at 85°C, and rolled up to prepare an aramid coated diaphragm with hydrophobic functional properties. The moisture content off the machine is 1633.3 ppm.

[0064] Example 4

[0065] (1) Under nitrogen dry environment, add biphenyl aromatic diamine (2,2-bis-(4-aminophenyl)hexafluoropropane) and DMSO to a 500ml glass reactor at room temperature. After the biphenyl aromatic diamine is dissolved, the temperature in the system is maintained at 15°C. Then add isophthaloyl chloride to the system for polycondensation reaction. During the reaction, the stirrer maintains a speed of 500r / min. The isophthaloyl chloride added in the polycondensation reaction is 90% by weight of the total amount of isophthaloyl chloride added. During the reaction, the system temperature is 45°C and the reaction time is 30min. Then add the remaining 10% by weight of isophthaloyl chloride to the system for polycondensation reaction. During this process, the system temperature is controlled at 55°C and the reaction time is 15min. After the polycondensation reaction is completed, add a neutralizer to the system and adjust the pH value of the system to 8. After the neutralization reaction, a DPMIA polymer solution is obtained with a viscosity of 1350 Pa•s and a molecular weight distribution of Mw / Mn=1.34. The solid content of the DPMIA polymerization solution is 15%, and the molar ratio of diphenyl aromatic diamine and isophthaloyl chloride in the preparation process of the DPMIA polymerization solution is 1:1.05.

[0066] (2) Under nitrogen dry environment, m-phenylenediamine and DMSO were added to a 500 ml glass reactor at room temperature. After m-phenylenediamine was dissolved, the temperature in the system was maintained at 15°C. Then, isophthaloyl chloride was added to the system for polycondensation reaction I. During the reaction, the stirrer maintained a speed of 500 r / min. The isophthaloyl chloride added in polycondensation reaction I was 90% by weight of the amount of acyl chloride added. During the reaction, the system temperature was controlled at 45°C and the reaction time was 30 min. Then, the remaining 10% by weight of isophthaloyl chloride was added to the system for polycondensation reaction II. During this process, the system temperature was controlled at 55°C and the reaction time was 15 min. After the polycondensation reaction was completed, a neutralizer was added to the system to adjust the pH value of the system to 8.0. After the neutralization reaction, PMIA polymer solution was obtained with a viscosity of 750 Pa•s and a molecular weight distribution of Mw / Mn=1.44. The solid content of the PMIA polymerization solution is 15%, and the molar ratio of isophthaloyl chloride to metaphenylenediamine in the preparation process of the PMIA polymerization solution is 1:1.

[0067] (3) Mixing the DPMIA polymer solution and the PMIA polymer solution, wherein the solid weight ratio of DPMIA to PMIA is 10:90; then adding DMSO for dilution to obtain a coating solution with a solid content of 3 wt %.

[0068] (4) The coating liquid is coated on a coating machine at a coating speed of 50 m / min, and is formed through a coagulation bath, wherein the NMP content in the coagulation bath is 65% and the temperature is 15°C. A coated diaphragm with an aramid coating structure is obtained through a non-solvent induced phase separation method. The aramid coated diaphragm is washed with water at 30°C, dried at 55°C, shaped at 55°C, and rolled up to prepare an aramid coated diaphragm with hydrophobic functional properties. The moisture content off the machine is 1702.7 ppm.

[0069] Comparative Example 1

[0070] The coated diaphragm was prepared by the same method as in Example 2, except that: PMIA polymerization liquid was not added to the coating liquid of this comparative example 1, but only DPMIA polymerization liquid was added. The specific preparation process is as follows:

[0071] (1) Same as step (1) in Example 2.

[0072] (2) DMAc was added to the DPMIA polymer solution prepared in step (1) above to dilute it, thereby obtaining a coating solution with a solid content of 9 wt %.

[0073] (3) The coating liquid is coated on a coating machine at a coating speed of 60 m / min, and is formed through a coagulation bath, wherein the DMAc content in the coagulation bath is 60% and the temperature is 10°C. A coated diaphragm with an aramid coating structure is obtained through a non-solvent induced phase separation method. The aramid coated diaphragm is washed with water at 20°C, dried at 70°C, shaped at 85°C, and rolled up to prepare an aramid coated diaphragm with hydrophobic functional properties. The moisture content off the machine is 493.8 ppm.

[0074] Comparative Example 2

[0075] The coated diaphragm was prepared by the same method as in Example 1, except that: the coating liquid of Comparative Example 2 did not contain DPMIA polymer solution, but only PMIA polymer solution. The specific preparation process was as follows:

[0076] (1) Prepare PMIA polymer solution in the same manner as step (2) in Example 1.

[0077] (2) DMAc was added to the PMIA polymerization solution for dilution to obtain a coating solution with a solid content of 9 wt%

[0078] (3) The coating liquid was coated on a coating machine at a coating speed of 60 m / min, and then formed in a coagulation bath, wherein the DMAc content in the coagulation bath was 70% and the temperature was 15°C. A coated diaphragm with an aramid coating structure was obtained by a non-solvent induced phase separation method. After washing with water at 30°C, drying at 65°C, shaping at 80°C, and winding, an aramid coated diaphragm with hydrophobic functional properties was prepared, and the moisture content off the machine was 3570.6 ppm.

[0079] Comparative Example 3

[0080] The coated diaphragm was prepared by the same method as in Example 1, except that the amount of DPMIA in the coating liquid of Comparative Example 3 was increased, and the solid weight ratio of DPMIA to PMIA in the coating liquid of Comparative Example 2 was 20:80. The specific preparation process was as follows:

[0081] (1) The DPMIA polymer solution was prepared in the same manner as in step (1) of Example 1.

[0082] (2) The PMIA polymer solution was prepared in the same manner as in step (2) of Example 1.

[0083] (3) Mixing the DPMIA polymer solution and the PMIA polymer solution, wherein the solid weight ratio of DPMIA to PMIA is 20:80; then adding DMAc for dilution to obtain a coating solution with a solid content of 9 wt %.

[0084] (4) The coating liquid was coated on a coating machine at a coating speed of 60 m / min, and then formed in a coagulation bath, wherein the DMAc content in the coagulation bath was 70% and the temperature was 15°C. A coated diaphragm with an aramid coating structure was obtained by a non-solvent induced phase separation method. After washing with water at 30°C, drying at 65°C, shaping at 80°C, and winding, an aramid coated diaphragm with hydrophobic functional properties was prepared, and the moisture content off the machine was 1103.4 ppm.

[0085] Comparative Example 4

[0086] The coated diaphragm was prepared by the same method as in Example 1, except that the amount of DPMIA in the coating solution of Comparative Example 3 was reduced, and the solid weight ratio of DPMIA to PMIA in the coating solution of Comparative Example 2 was 2:98. The specific preparation process was as follows:

[0087] (1) The DPMIA polymer solution was prepared in the same manner as in step (1) of Example 1.

[0088] (2) The PMIA polymer solution was prepared in the same manner as in step (2) of Example 1.

[0089] (3) The DPMIA polymer solution and the PMIA polymer solution were mixed, wherein the solid weight ratio of DPMIA to PMIA was 2:98; DMAc was then added for dilution to obtain a coating solution with a solid content of 9 wt %.

[0090] (4) The coating liquid was coated on a coating machine at a coating speed of 60 m / min, and then formed in a coagulation bath, wherein the DMAc content in the coagulation bath was 70% and the temperature was 15°C. A coated diaphragm with an aramid coating structure was obtained by a non-solvent induced phase separation method. After washing with water at 30°C, drying at 65°C, shaping at 80°C, and winding, an aramid coated diaphragm with hydrophobic functional properties was prepared, and the moisture content off the machine was 3347.1 ppm.

[0091] Comparative Example 5

[0092] The coated diaphragm was prepared by the same method as in Example 1, except that the concentration of the coagulation bath was reduced. In Comparative Example 5, the concentration of the coagulation bath was 30%. The specific preparation process was as follows:

[0093] (1) The DPMIA polymer solution was prepared in the same manner as in step (1) of Example 1.

[0094] (2) The PMIA polymer solution was prepared in the same manner as in step (2) of Example 1.

[0095] (3) Prepare a coating liquid in the same manner as step (3) in Example 1;

[0096] (4) The coating liquid is coated on a coating machine at a coating speed of 60 m / min, and is formed through a coagulation bath, wherein the DMAc content in the coagulation bath is 30% and the temperature is 15°C. A coated diaphragm with an aramid coating structure is obtained through a non-solvent induced phase separation method. The aramid coated diaphragm is washed with water at 30°C, dried at 65°C, shaped at 80°C, and rolled up to prepare an aramid coated diaphragm with hydrophobic functional properties. The moisture content off the machine is 1700.9 ppm.

[0097] Comparative Example 6

[0098] The coated diaphragm was prepared by the same method as in Example 1, except that the coagulation bath temperature was increased, and the coagulation bath concentration in this comparative example 5 was 30%. The specific preparation process was as follows:

[0099] (1) Prepare a DPMIA polymerization solution by the same method as step (1) in Example 1;

[0100] (2) Prepare PMIA polymerization solution by the same method as step (2) in Example 1;

[0101] (3) Prepare a coating liquid in the same manner as step (3) in Example 1;

[0102] (4) The coating liquid is coated on a coating machine at a coating speed of 60 m / min, and is formed through a coagulation bath, wherein the DMAc content in the coagulation bath is 70% and the temperature is 40°C. A coated diaphragm with an aramid coating structure is obtained through a non-solvent induced phase separation method. The aramid coated diaphragm is washed with water at 30°C, dried at 65°C, shaped at 80°C, and rolled up to prepare an aramid coated diaphragm with hydrophobic functional properties. The moisture content off the machine is 1677.2 ppm.

[0103] The coated diaphragms prepared in the above examples and comparative examples were subjected to performance tests, and the coated diaphragms were used to prepare soft-pack laminated batteries, and the diaphragm conductivity and battery performance tests were performed, wherein NCM811 was used as the positive electrode, artificial graphite was used as the negative electrode, and the electrolyte used was an electrolyte in which the lithium salt was lithium hexafluorophosphate, the solvent was ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate, and the additive was vinylene carbonate. The specific test results are shown in Tables 1, 2 and 3.

[0104] The diaphragm testing standards involved are as follows:

[0105] Thickness testing standard: GB / T 36363-2018;

[0106] Tensile strength test standard: GB / T 36363-2018;

[0107] Air permeability test standard: GB / T 36363-2018;

[0108] Puncture strength test standard: GB / T 36363-2018;

[0109] Thermal shrinkage test standard: GB / T 36363-2018;

[0110] Liquid absorption test standard: GB / T 13542.2-2009;

[0111] Film rupture temperature test standard: GB / T 36800.1-2018;

[0112] Ionic conductivity test standard: GB / T 36363-2018;

[0113] Battery high and low temperature test standard: GB31241-2022.

[0114] Table 1 Physical property test data of coated diaphragm of Examples 1-4

[0115]

[0116] Table 2 Physical property test data of coated diaphragms of comparative examples 1-6

[0117]

[0118] Table 3 Electrochemical performance test data of coated diaphragm

[0119]

[0120] It can be seen from the data in the above table that the coated diaphragms prepared according to the preparation method of Example 1 to Example 4 have good mechanical properties, thermal stability, hydrophobic properties and high ionic conductivity, and after being used in batteries, have good low-temperature discharge performance. Figure 2 The SEM image of the coated diaphragm prepared in Example 1 is shown in FIG. Figure 2 It can be seen that the coating layer presents a regular and uniform dendritic network distribution, with a lower air permeability increment, which is beneficial to the transmission of lithium ions. At the same time, the coating can provide support, enhance the mechanical properties of the coating film, and improve the electrolyte absorption and liquid retention properties of the diaphragm.

[0121] From the comparison of the experimental data of Comparative Example 1 and Example 2, it can be seen that if the prepared coating liquid contains only DPMIA polymer solution, the adhesion between the coating layer and the base film will decrease, resulting in a decrease in the peel strength of the coating, because in the molecular chain structure of DPMIA, the distance between the amide bonds is elongated, which will reduce the molecular bond force between the coating and the base film.

[0122] From the comparison of the experimental data of Comparative Example 2 and Example 1, it can be seen that if the prepared coating liquid contains only PMIA polymer solution, the moisture content of the coated diaphragm will be too high, because PMIA molecules contain a large number of amide bonds, which themselves have a certain water absorption capacity and are not easy to dry and dehydrate during the coating process.

[0123] From the comparison of the experimental data of Comparative Example 3 and Example 1, it can be seen that if the proportion of DPMIA in the prepared coating liquid increases, the peel strength of the coating will decrease, because the increase in the DPMIA content will reduce the number of molecular amide bonds in the mixed system, which will reduce the hydrogen bonding effect between the coating and the base film.

[0124] From the comparison of the experimental data of Comparative Example 4 and Example 1, it can be seen that if the proportion of DPMIA in the prepared coating liquid is reduced, the moisture content of the coated diaphragm will be too high, because the PMIA molecule contains a large number of amide bonds, which have a certain water absorption capacity and are not easy to dry and dehydrate during the coating process. Therefore, the use of the DPMIA and PMIA dosage ratio defined in the present invention is more conducive to obtaining a coated diaphragm with excellent comprehensive performance.

[0125] From the comparison of the experimental data of Comparative Example 5 and Example 1, it can be seen that: if the concentration of the coagulation bath is reduced, the molding speed is faster, the non-uniformity of the pore structure of the coating increases, which is not conducive to better molding of the coating liquid on the surface of the base membrane, and the interaction force between the coating and the base membrane is reduced, resulting in smaller pores on the coating surface, and a decrease in the air permeability of the coated diaphragm, which in turn leads to a decrease in ionic conductivity.

[0126] From the comparison of the experimental data of Comparative Example 6 and Example 1, it can be seen that if the coagulation bath temperature is increased, the molding speed will also be accelerated, resulting in poor coating uniformity of the coating film, a large number of hollow holes will be generated, and the mechanical properties of the coating film will be reduced. Therefore, the coagulation bath conditions of the present invention are more conducive to obtaining a coated diaphragm with excellent performance.

[0127] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0128] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for preparing a hydrophobic aramid coated diaphragm for a lithium ion battery, characterized in that: The preparation method comprises: uniformly coating the coating liquid on the base film, forming the base film through a coagulation bath, and then washing, drying, shaping, and rolling to prepare a hydrophobic aramid coated diaphragm; the coagulation bath is an aqueous solution of an organic solvent, the mass concentration of the organic solvent in the coagulation bath is 60%-80%, and the temperature of the coagulation bath is 10-20°C; The preparation method of the coating liquid is: S1. Preparation of DPMIA polymerization solution and PMIA polymerization solution: Preparation of DPMIA polymer solution: biphenyl aromatic diamine monomer and isophthaloyl chloride are subjected to polycondensation reaction in an organic solvent, and DPMIA polymer solution is obtained after neutralization and degassing; Preparation of PMIA polymer solution: m-phenylenediamine monomer and isophthaloyl chloride are subjected to polycondensation reaction in an organic solvent, and then neutralized and degassed to obtain PMIA polymer solution; S2. Preparation of coating liquid: DPMIA polymerization liquid and PMIA polymerization liquid are mixed and diluted with an organic solvent to obtain the coating liquid; in the coating liquid, the mass ratio of DPMIA to PMIA is (5-10): (90-95); The biphenyl aromatic diamine monomer is 2,2'-bis-[4-(4-aminophenoxy)phenyl]propane, 4,4'-diamino-2,2'-bistrifluoromethylbiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl; The solid content of the coating liquid is 3wt%-15wt%; When preparing the DPMIA polymerization solution, the molar ratio of the biphenyl aromatic diamine monomer to isophthaloyl chloride is 1:(1-1.05), and isophthaloyl chloride is added to the reaction system in batches for polycondensation reaction, and the polycondensation reaction temperature is 45-55°C; When preparing PMIA polymerization liquid, the molar ratio of m-phenylenediamine monomer to isophthaloyl chloride is 1:(1-1.05), and isophthaloyl chloride is added to the reaction system in batches for polycondensation reaction, and the polycondensation reaction temperature is 45-55°C; The washing temperature is 20-40°C; the drying temperature is 55-85°C, the drying speed is 50-120 m / min; the setting temperature is 55-85°C.

2. The method for preparing a hydrophobic aramid coated diaphragm for a lithium ion battery according to claim 1, characterized in that: The organic solvent is at least one of DMAc, DMF, NMP and DMSO.

3. A hydrophobic aramid coated diaphragm for a lithium ion battery, characterized in that: The coated diaphragm is prepared according to the preparation method according to any one of claims 1-2.

Citation Information

Patent Citations

  • Meta-aramid fiber coating slurry, preparation method thereof and battery diaphragm

    CN117060007A

  • Glued diaphragm uniform in coating and not prone to powder falling and preparation method thereof

    CN118431664A

  • Modified aramid polymer with polyimide structure, aramid membrane casting solution, lithium battery diaphragm, preparation method and lithium battery

    CN111234224A